Some Factors Associated with Ovarian Disorders of Dairy Cattle in Northern Vietnam - S. T. Long; P. V. Gioi; N. T. Suong (Tropical Animal Science Journal, 2021)
This research’s objectives were to assess the risk factors associated with ovarian disorders in dairy cattle in Hanoi Capital, Ha Nam Province, Vinh Phuc Province, and Moc Chau District in Son La Province. The ovarian diseases were evaluated by rectal palpation combined with information collected based on the questionnaire and surveys. Records of feeding management and ovarian disorders were comprising of persistent corpus luteum (PCL), cystic ovarian disease (COD), inactive ovary (IO) from 818 females, including heifers and cows from the first to the eighth parities. A multinomial logistic regression procedure in SAS9.0 was applied for data analysis. The results have shown that the changes of region, age classes, housing condition, and body condition scores were associated with the odds of suffering from dairy cattle’s ovarian disorder categories. The cows got the odds of suffering from PCL in the old age or fatter condition, and IO at the younger or angular cows. When cattle were confined in simple houses or laid on rubber bedding, they suffered from IO, but they tended to get the odds of suffering from PCL when the cattle were raised in modern houses or laid on concrete bedding. In conclusion, region, parity, body condition score, housing type, and bedding material affect ovarian disorders in dairy cattle in northern Vietnam.